Question and Answer Relationship Strategy (QAR): Elevating EFL Students’ Reading Comprehension - Alvionita, Widya; Anggreni, Afrillia; Munir, Syahrul; Suriaman, Aminah (Journal of English Language and Education, 2025)
Reading comprehension still became a problematic competence for some EFL students in High School level. Many scholars have implemented various cognitive reading strategies. Thus, the objective of this research is to explore whether or not the implementation of Question-and-Answer Relationship Strategy (QAR) can boost students’ reading comprehension of eleventh grade of SMA Negeri 1 Sindue.  Narrative text in terms of local folklore was focused on this research and limited in literal and inferential level of understanding. A quasi-experimental research design was utilized. The researchers applied a random sampling technique and selected XI G as an experimental class with 22 students and XI C as a control class with 22 students. Then, tests were used as research instruments which consisted of pretest and post-test. Furthermore, the researchers used SPSS (Statistical Package for Social Sciences) 29.0.2.0 to analyse the data. The data prove that the mean score of the experimental class was higher than the mean score of the control class. In addition, the result of sig. (2-tailed) is lower than 0.05. Therefore, it can be indicated that the hypothesis is accepted. Thus, this research concludes that Question and Answer Relationship Strategy can effectively enhance the students’ reading comprehension of eleventh grade of SMA Negeri 1 Sindue.